Evaluation of residents’ quality of life of low cost housing programme in Tangerang city - Andi Wibowo,; Hamzah Jusoh,; Habibah Ahmad,; Jalaluddin Abdul Malek, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Low cost housing (Rusunawa) Programme in Indonesia has been intended to serve low income citizens and in the same time to eradicate slum and squatter settlements in city areas. Some studies about Rusunawa Programme in Indonesia found some problems in Rusunawa affecting Rusunawa residents’ quality of life. This study is conducted to evaluate quality of life of Rusunawa residents in Tangerang City. Health, safety, convenience, income, education and social relation are indicators used to evaluate quality of life. The study used mix methods using survey and interviews. Interviews were conducted to city government officials, rusunawa management, rusunawa residents and people living around the rusunawa and survey questionnaires were distributed to 289 Rusunawa residents. The study shows that Rusunawa residents are satisfied with all aspects of quality of life but income. To overcome the problem, government needs to provide more empowerment programme for residents. Mean comparison between respondents in Rusunawa Manis and Rusunawa Gebang shows that Respondents in Manis are more convenient and have better social relation than that of in Gebang. On the contrary, respondents stated that Gebang is safer than Manis. There is no significant different in opinion between low and high income respondents.